A Study on Awareness and Adaptability of Economic Value Added Concept in Indian Banking Sector - Satish, R.; Rao, S. S. (Indian Journal of Finance, 2010)
The fundamental principle of capitalism is that organizations are expected to take financial capital from shareholders and make it worth more. The success of the firm depends on its proficient management having theoretically sound knowledge of time-honoured tools for planning, decision-making, forecasting and monitoring. Developing new-fangled financial and management accounting tool is an incredibly contemporary subject matter for both the academicians engaged in business research and financial consultants in practice. During the last few years, the field of finance has become even more prominent. The concept of the Economic Value Added is similar to the traditional accounting concept of Residual Income [RI]. The concept emerges in several variations and incarnations including the trade-marked Stern Stewart&Co's EVA with its copious accounting adjustments. Corresponding to Stewart [1991] view, EVA is a residual return measure that subtracts the cost of invested capital from net operating profit after tax.